2019
DOI: 10.1029/2019gl084678
|View full text |Cite
|
Sign up to set email alerts
|

Electrification of Experimental Volcanic Jets with Varying Water Content and Temperature

Abstract: Volcanic lightning-a near ubiquitous feature of explosive volcanic eruptions-possesses great potential for the analysis of volcanic plume dynamics. To date, the lack of quantitative knowledge on the relationships between plume characteristics hinders efficient data analysis and application of the resulting parameterizations. We use a shock-tube apparatus for rapid decompression experiments to produce particleladen jets. We have systematically and independently varied the water content (0-27 wt%) and the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 64 publications
5
40
0
Order By: Relevance
“…Such global lightning detection data was used during the response to the eruption of the remote, and under-instrumented Bogoslof volcano in Alaska (Coombs et al, 2018), where lightning was detected from only roughly half of the ash-producing eruptions. Van Eaton et al (2020) showed that secondary ice-charging processes (Arason et al, 2011;Behnke et al, 2013;Van Eaton et al, 2016;Woodhouse & Behnke, 2014), rather than ash-charging processes (e.g., Houghton et al, 2013;James et al, 2000;Mendez Harper & Dufek, 2016;Mendez Harper et al, 2020;Stern et al, 2019), were likely responsible for the lightning detected by the global networks, and speculated that it was very likely that there was much more lightning and electrical activity that occurred that wasn't detected by the long-range VLF sensors. During this eruption, the global lightning data was a boon for the volcano response effort, though the latency between eruption and first lightning detection varied from one minute to one hour.…”
mentioning
confidence: 99%
“…Such global lightning detection data was used during the response to the eruption of the remote, and under-instrumented Bogoslof volcano in Alaska (Coombs et al, 2018), where lightning was detected from only roughly half of the ash-producing eruptions. Van Eaton et al (2020) showed that secondary ice-charging processes (Arason et al, 2011;Behnke et al, 2013;Van Eaton et al, 2016;Woodhouse & Behnke, 2014), rather than ash-charging processes (e.g., Houghton et al, 2013;James et al, 2000;Mendez Harper & Dufek, 2016;Mendez Harper et al, 2020;Stern et al, 2019), were likely responsible for the lightning detected by the global networks, and speculated that it was very likely that there was much more lightning and electrical activity that occurred that wasn't detected by the long-range VLF sensors. During this eruption, the global lightning data was a boon for the volcano response effort, though the latency between eruption and first lightning detection varied from one minute to one hour.…”
mentioning
confidence: 99%
“…All rights reserved. Stern et al [2019], the collision energies produced in the tumbler are more representative of conditions in convective columns transitioning to mature plumes than those in the gas-thrust region. The low energy interactions between particles did not produce obvious mechanical modification to the grains (as quantified by optical microscopy analysis performed before and after an experiment).…”
Section: Methodsmentioning
confidence: 99%
“…%) in a 300 o C jet. Stern et al [2019] also explored the role of temperature within the range of 25 -320 o C and report a moderate increase in electrical activity with increasing temperature.…”
Section: Confidential Manuscript Submitted To Journal Of Geophysical Research -Atmospheresmentioning
confidence: 99%
See 2 more Smart Citations